Les morts qui comptent - Simon Varaine (Communication)
Although the lack of equal media attention for victims of conflict has been the subject of theoretical and normative discussions, the explanations offered up have yet to be empirically proven. The author analyzes the media attention paid by two newspapers of record, Le Monde (France) and Le Devoir (Canada), to deaths by collective violence among 64 nationalities in 2012. His analysis shows that newspapers tend to overmediatize victims from rich countries in the same cultural sphere that are the focus of their news coverage. Other classic hypotheses remain to be verified. Clearly, there is a need to bring to bear the differences between different media organizations in general theories of bias in international coverage.